Optimizing Social Media in Building Brand Awareness at the Nda Sha Snacks UKM in Sumorame Village, Sidoarjo: Optimalisasi Media Sosial dalam Membangun Brand Awareness pada UKM Jajanan Nda Sha Desa Sumorame Sidoarjo - Dyah Tuhrotul Fuada; Adhelia Cahya Puspita; Muhammad Sonhaji; Rizqy Mutawakkil Ngalalloh (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Social media platforms serve as vital instruments for micro-enterprises to expand market reach. Specific Background For culinary micro-enterprises like Jajanan Nda Sha, Instagram offers a visual-heavy channel to engage local consumers. Knowledge Gap However, high posting frequency often fails to build brand awareness due to unanalyzed metric data and inconsistent visual strategies. Aims This study analyzes social media optimization to build brand awareness through a structured, data-driven approach. Results Findings reveal that integrating Instagram Insight analytics, defining a uniform visual identity, leveraging interactive story features, targeting local hashtags, and monitoring key performance indicators substantially improve performance. Novelty This work establishes a quantitative metric-guided framework tailored specifically for resource-constrained culinary micro-enterprises. Implications The proposed strategy provides actionable guidelines for small business owners to transform basic social media presence into measurable promotional effectiveness. Key Findings Highlights Low engagement stems from intuitive posting schedules rather than performance metric analysis. Combining visual consistency with interactive features drives audience engagement effectively. Quantitative KPI benchmarks ensure sustainable social media marketing for local businesses. Keywords: Social Media Optimization, Instagram, Brand Awareness, Micro-Enterprises, Digital Strategy